The use of fiber bragg grating coated with polyimide for CO2 gas sensor - Irawan, Dedi; Saktioto, Saktioto; Azhar, Azhar; Sutoyo, Sutoyo; Sahal, Muhammad; Hanto, Dwi; Widiyatmoko, Bambang (Bulletin of Electrical Engineering and Informatics, 2025)
This study presents the application of fiber bragg grating (FBG) sensors coated with polyimide for detecting carbon dioxide (CO₂) gas, employing both theoretical and experimental approaches. The basic FBG components were coated with polyimide layers of varying thicknesses. Subsequently, the fabricated FBG sensors were characterized using an optical interrogator system with four channels. Furthermore, the sensor was tested for CO₂ detection at a working temperature of 47 °C. Experimental data showed that the FBG sensor coated with polyimide layers of 10 nm, 15 nm, and 20 nm demonstrated sensitivities of 1.9 ppm, 1.84 ppm, and 1.8 ppm, respectively. In contrast, the uncoated FBG sensor exhibited a higher sensitivity of 3 ppm. Increasing the coating thickness beyond 20 nm leads to a decrease in sensor sensitivity. The findings suggest that an optimal polyimide coating thickness for CO₂ detection using FBG sensors is around 20 nm. Achieving high sensitivity in CO₂ gas sensors is crucial for their effective use across a broad range of applications.